Coatings with a Mole-hill Structure of Nanoparticle-Raspberry Containers for Surfaces with Abrasion-Refreshable Reservoir Functionality - Ballweg, Thomas; Gellermann, Carsten; Mandel, Karl (ACS Applied Materials and Interfaces, 2015)
Active silica nanoparticle-based raspberry-like container depots for agents such as antimicrobial substances are presented. The nano raspberry-containers are integrated into coatings in a way that they form a mole-hill structure; i.e., they are partly standing out of the coating. As an application example, it is demonstrated that the containers can be filled with antimicrobially active agents such as nano ZnO or Ag or organic molecules such as thymol. It is demonstrated that the containers can be partly chopped-off via abrasion by rubbing over the surface. This mechanism proves to be an attractive approach to render surfaces refreshable. A first proof of principle for antimicrobial activity of the intact containers in the coatings and the abrasion treated, chopped-off (and thereby reactivated) containers is demonstrated.
CRIS-Team Scopus Importer:2020-04-02
Keywords: antimicrobial; nanocontainers; nanoraspberries; reservoirs; structured coatings